2002
DOI: 10.1080/01944360208976273
|View full text |Cite
|
Sign up to set email alerts
|

Underestimating Costs in Public Works Projects:Error or Lie?

Abstract: This article presents results from the first statistically significant study of cost escalation in transportation infrastructure projects. Based on a sample of 258 transportation infrastructure projects worth $90 billion (U.S.), it is found with overwhelming statistical significance that the cost estimates used to decide whether important infrastructure should be built are highly and systematically misleading. The result is continuous cost escalation of billions of dollars.The sample used in the study is the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
1,001
3
34

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,167 publications
(1,059 citation statements)
references
References 22 publications
21
1,001
3
34
Order By: Relevance
“…It does not need much stretch of the imagination to see that the alternatives can be presented in such a way that the most favourable alternative, from the developer's point of view, appears to be the best, or possibly the only, choice (intentionally or unintentionally). Flyvbjerg et al (2002) discuss whether the systematic underestimation of costs in public projects is a result of errors or lies. Costs were underestimated in 90% of the 258 transportation infrastructure projects in their study.…”
Section: Can Eia Predictions Ever Be Objective and Accurate?mentioning
confidence: 99%
“…It does not need much stretch of the imagination to see that the alternatives can be presented in such a way that the most favourable alternative, from the developer's point of view, appears to be the best, or possibly the only, choice (intentionally or unintentionally). Flyvbjerg et al (2002) discuss whether the systematic underestimation of costs in public projects is a result of errors or lies. Costs were underestimated in 90% of the 258 transportation infrastructure projects in their study.…”
Section: Can Eia Predictions Ever Be Objective and Accurate?mentioning
confidence: 99%
“…Overconfidence affects the judgments of physicians (Oskamp 1965), entrepreneurs (Cooper et al 1988), bridge players (Keren 1987), government planners (Flyvbjerg et al 2002), investors (Statman et al 2006), and basketball players (Jagacinski et al 1977), to name but a few examples. Research has identified overconfidence in tests of declarative knowledge, bets, and predictions of the future (Ben-David et al 2013, Massey et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Flyvbjerg et al (2002) when examining transport projects found that 90% had the cost overruns. Meng (2012) found, as a result of his research that 35.6% of projects are not completed on time and that 88.2% have some type of defect.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this research, the analysis units chosen were economic infrastructure projects whose risk management processes, and subsequent performances, are far from the desired (McKim et al, 2000;Flyvbjerg et al, 2002;Shenhar & Dvir, 2007). In this way, five cases have been selected and evaluated by the technique of synthesis of cross cases (Yin, 2015).…”
Section: /43mentioning
confidence: 99%